Performance analysis of differential spin hall effect (DSHE)-MRAM-based logic gates. Issue 4 (16th October 2019) - Tankwal, Piyush; Nehra, Vikas; Prajapati, Sanjay; Kaushik, Brajesh Kumar
Abstract : Purpose: The purpose of this paper is to analyze and compare the characteristics of hybrid conventional complementary metal oxide semiconductor/magnetic tunnel junction (CMOS/MTJ) logic gates based on spin transfer torque (STT) and differential spin Hall effect (DSHE) magnetic random access memory (MRAM). Design/methodology/approach: Spintronics technology can be used as an alternative to CMOS technology as it is having comparatively low power dissipation, non-volatility, high density and high endurance. MTJ is the basic spin based device that stores data in form of electron spin instead of charge. Two mechanisms, namely, STT and SHE, are used to switch the magnetization of MTJ. Findings: It is observed that the power consumption in DSHE based logic gates is 95.6% less than the STT based gates. DSHE-based write circuit consumes only 5.28 fJ energy per bit. Originality/value: This paper describes how the DSHE-MRAM is more effective for implementing logic circuits in comparison to STT-MRAM.